Нові давньоруські пам'ятки околиць Києва - Козюба, В.К. (Археологія і давня історія України, 2017)
У публікації подано опис 10 пам'яток Х —ХІІІ ст.
(7 з яких відкрито вперше) з околиць давнього Києва, обстежених автором у 2011—2014 рр. На начало 2017 г. на территории Киева в его современных административных границах известно
более 60 археологических памятников Х—ХІІІ вв.,
среди которых городища, поселения, могильники
(курганные и грунтовые), монастыри и пещеры.
В публикации приводятся сведения о 10 памятниках (8 поселений и 2 курганных могильника), большинство из которых были открыты автором во время разведок 2011—2014 гг. К описанию памятников и выявленной на них керамике прилагаются их планы.
Обнаружение неизвестных ранее памятников древнерусского времени на околицах древнего Киева дает новые материалы для изучения характера и
времени заселения пригородных зон столицы Руси. More than 60 archaeological sites of 10—13 centuries
are registered on the territory of Kiev in its modern
administrative borders at the beginning of 2017,
including towns, villages, cemeteries (barrows and
burial grounds), monasteries and caves.
The publication provides information about 10 sites
(8 settlements and 2 mound cemeteries), generally discovered
by the author during surveys of 2011—2014.
The description of sites is complemented by plans and the artifacts drawings.
The discovery of previously unknown sites of Old Rus’sian time on the outskirts of the ancient Kiev provides
new materials for the study of the nature and time of settlement of residential suburbs of the capital of Rus’.